2020
DOI: 10.1016/j.ijwd.2020.07.011
|View full text |Cite
|
Sign up to set email alerts
|

The possible role of oral microbiome in autoimmunity

Abstract: Objective The human microbiome refers to the entire habitat, including microorganisms, their genomes and the surrounding environmental conditions of the microbial ecosystem. When the equilibrium between microbial habitats and host is disturbed, dysbiosis is caused. The oral microbiome (OMB) has been implicated in the manifestation of many intra- and extraoral diseases. Lately, there has been an intense effort to investigate and specify the relationship between microbial complexes, especially that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 100 publications
0
12
0
Order By: Relevance
“…The human oral cavity is composed of unique niches colonized by a variety of microorganisms, including bacteria, fungi, viruses, and archaea, which create a rich microbial community known as the oral microbiome [ 1 ]. These communities of microbes are highly dynamic and responsible for various functions that can both maintain and deplete oral health.…”
Section: Introductionmentioning
confidence: 99%
“…The human oral cavity is composed of unique niches colonized by a variety of microorganisms, including bacteria, fungi, viruses, and archaea, which create a rich microbial community known as the oral microbiome [ 1 ]. These communities of microbes are highly dynamic and responsible for various functions that can both maintain and deplete oral health.…”
Section: Introductionmentioning
confidence: 99%
“…From Figure 1 , the metabolic profile of the Salmonella group was gradually away from the healthy state, indicating that the impact of inflammation of the body was relative high on the metabolism. Previous studies suggested that intestinal metabolites can be involved in the control of inflammation by controlling mechanisms of neutrophil chemotaxis, and their activity may affect the regulation of inflammatory processes in enteritis [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stress contributes to increase gut permeability, and this may explain why it often precedes RA flares. Sex hormones also interact with the equilibrium between microbial habitats and the host immune response [89]. Therefore, longitudinal analyses of oral, gut, blood, and synovium microbiomes might be separately analyzed in males and females, and in young versus old, especially as RA is mostly a female disorder (three of four of patients are female).…”
Section: Stress Hormonal Status and Tobaccomentioning
confidence: 99%